Vittoria Colonna poetry, religion, art, impact - Cox, Virginia 1962-; McHugh, Shannon (Gendering the late medieval and early modern world, 2022)
This edited collection presents fresh and original work on Vittoria Colonna, perhaps the outstanding female figure of the Italian Renaissance, a leading Petrarchist poet, and an important figure in the Italian Reform movement. Until recently best known for her close spiritual friendship with Michelangelo, she is increasingly recognized as a powerful and distinctive poetic voice, a cultural and religious icon, and an important literary model for both men and women. This volume comprises compelling new research by established and emerging scholars in the fields of literature, book history, religious history, and art history, including several studies of Colonna's influence during the Counter-Reformation, a period long neglected by Italian cultural historiography. The Colonna who emerges from this new reading is one who challenges traditional constructions of women's place in Italian literature; no mere imitator or follower, but an innovator and founder of schools in her own right